PENGARUH MEDIA BONEKA TANGAN TERHADAP KETERAMPILAN MENYIMAK DONGENG SISWA KELAS 1 SD LABSCHOOL UNESA - Mohammad Setyo Wardono; Rikke Kurniawati (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
This research emerges from the observations and experiences of researchers that hand puppets are one of the exciting media and foster enthusiasm for learning for low-grade students in elementary schools. On the other hand, hand puppet media invites students to be more active in communicating. The purpose of this study was to determine the effect of hand puppet media on the listening skills of students in the lower grades. This research uses Quasi Experimental design method. Sampling technique in this research is purposive sampling. Data analysis techniques consist of validation, reliability, normality test, and hypothesis testing. It can be proved through hypothesis test using T-test with tcount>ttable is 9,871> 2,016 with significant level 5%. Based on the results of the study there is a significant influence of the use of hand pupet media scrutinize of first grader SD Labschool Unesa.